Diaspora Bugis dan Ketegangan Maritim di Kutai-Pasir: Kajian Historis Konflik Laut di Kalimantan Timur abad ke-18-19 - Thamara Nur Salsabila; Agussalim Baharuddin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This Study explore the study of The Bugis people’s migration from south sulawesi to East Kalimantan on their sattlement in Kutai dan Pasir from the 18th through 19th centuries. It looks at how the Buginese diaspora established independent groups, traded and developed political clouth through smart partnerships like marriages with local elites, all motivated by marine culture and economic aspirations. Internal disputes among Bugis factions, particularly over taxation and port countrol, and tentions with local authorities were frequently the results of these developments. In oder to increase their power in the area, the Dutch Colonial authorities kept an eye on these conflicts and accosianally got involved. This study emhasises how the Bugis significantly influenced power dynamics and coastal administration in East Kalimantan throughout both indigenous and colonial regimes, drawing on historical documents, open access academic sources and Buginese manuscripts.